The Sinai : a physical geography - Greenwood, Ned H., 1932- (ACLS Humanities E-Book., 1997)
In this book, Ned Greenwood offers a complete, up-to-date physical geography of Sinai. After an introductory chapter that situates Sinai within world history and geography, he focuses in detail on the following areas: plate tectonics and geology, geomorphology and drainage, weather and climate, soils, and biogeography. In the concluding chapter, Greenwood considers the human geography of Sinai, including the pressures currently posed by population growth, political extremism, and environmental constrictions on development. He offers a fully rounded picture of the physical environment of Sinai that will be vital reading for everyone concerned about the future of this strategic yet fragile land.